Managing the managers managing people: Lessons for recreation and water management in protected areas - Ingram, C.; Hughes, Michael (Wageningen University and Research Centre, 2010)
Many of Australia’s critical urban water resources are located within protected areas, originally reserved for their timber production, recreation and aesthetic values. Later, these areas were also recognised for their conservation value and as reliable, potable water supplies. This paper presents a case study of water source protection planning in urban water catchments and impoundments in the south west of Western Australia and the impacts on recreation and tourism access in protected areas. Inland water catchments in the Southwest of Western Australia have historically been, and are currently, popular resources for public recreation. Recreation includes a broad range of leisure, pastime and entertainment activities ranging from passive through to active pursuits that vary in their character and potential for environmental impacts.